Genomic Analysis Provides New Insights Into Biotechnological and Industrial Potential of Parageobacillus thermantarcticus M1 - Yasar Yildiz, Songul; Finore, Ilaria; Leone, Luigi; Romano, Ida; Lama, Licia; Kasavi, Ceyda; Nicolaus, Barbara; Toksoy Oner, Ebru; Poli, Annarita (Frontiers in Microbiology, 2022)
Parageobacillus thermantarcticus strain M1 is a Gram-positive, motile, facultative anaerobic, spore forming and thermophilic bacterium, isolated from geothermal soil of the crater of Mount Melbourne (74o22’ S, 164o40’ E) during the Italian Antarctic Expedition occurred in Austral summer 1986–1987. Strain M1 demonstrated great biotechnological and industrial potential owing to its ability to produce exopolysaccharides (EPSs), ethanol and thermostable extracellular enzymes, such as an xylanase and a β-xylosidase, and intracellular ones, such as xylose/glucose isomerase and protease. Furthermore, recent studies revealed its high potential in green chemistry due to its use in residual biomass transformation/valorization and as an appropriate model for microbial astrobiology studies. In the present study, using a systems-based approach, genomic analysis of P. thermantarcticus M1 was carried out to enlighten its functional characteristics. The elucidation of whole-genome organization of this thermophilic cell factory increased our understanding of biological mechanisms and pathways, by providing valuable information on the essential genes related to the biosynthesis of nucleotide sugar precursors, monosaccharide unit assembly, as well as the production of EPSs and ethanol. In addition, gene prediction and genome annotation studies identified genes encoding xylanolytic enzymes that are required for the conversion of lignocellulosic materials to high-value added molecules. Our findings pointed out the significant potential of strain M1 in various biotechnological and industrial applications considering its capacity to produce EPSs, ethanol and thermostable enzymes via the utilization of lignocellulosic waste materials.